(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
There is a growing interest in developing natural skincare products with potent antioxidant properties to combat oxidative stress and premature aging. Objective: To formulate and evaluate an herbal antioxidant cream using papaya latex (Carica papaya) and banana peel extract (Musa spp.). Methods: Extraction of bioactive compounds from papaya latex and banana peel was performed, followed by antioxidant testing and cream formulation. The cream was evaluated for pH, viscosity, spreadability, phase separation, sensory qualities, and in vitro antioxidant activity. Results: Papaya latex exhibited greater antioxidant activity than banana peel extract. Creams demonstrated desirable physicochemical properties and increased antioxidant efficacy with higher extract concentrations. Conclusion: The herbal cream showed effective antioxidant potential, stability, and skin compatibility, offering a promising natural skincare alternative.